PENINGKATAN KESADARAN MASYAKAT TENTANG WISATA ALAM DAN KEBERSIHAN LINGKUNGAN DIDESA PARDOMUAN AJIBATA - Elfrido Lorensius Lumbangaol; Tambos August Sianturi; Jhon Sufriadi Purba (Abdi Jurnal Publikasi, 2026)
The Community Service Program (KPPM) that has been implemented has had a positive impact on the community, particularly in raising awareness about the importance of maintaining environmental cleanliness. Through this program, the people of Pardomuan Village—especially the youth—have gained a deeper understanding of the importance of keeping the environment clean as an integral part of daily life. As a result of this activity, the community has become more active in mutual cooperation and in working together with the local government to create a waste-free environment. Considering that environmental cleanliness is both a right and a shared necessity in maintaining a healthy environment, it is hoped that similar activities can be carried out sustainably to provide long-term benefits for both the local community and visiting tourists.